Incidence of Urinary Tract Infections with Bacterial Profile and Current Scenario of Antibiotic Susceptibility Pattern in the South India - Nagaraju, G. Venkata (Asian Journal of Pharmaceutics (AJP), 2025)
Urinary tract infections (UTIs) are currently emerging as a common infectious disease globally. UTI was commonly seen in women than men and in older people than the young people. Uropathogens such as Escherichia coli, Pseudomonas, Klebsiella, Citrobacter, Acinetobacter, proteus, Enterococcus, and Staphylococcus are responsible for the UTI. All these uropathogens developed the resistance to the most of the antibiotics gradually leads to the multidrug resistant UTI. This study aims to determine the current antibiotic susceptibility pattern of uropathogens and prevalence in the south India. Out of 784 samples, 296 samples showed significant growth of the bacteria. This study reveals that the prevalence rate is 37.56%. In samples with significant growth, the male with UTI is 48.90% and the female with UTI is 51.02% (P = 0.007). This study shows that major infections are caused by Gram-negative bacteria 88.51% than the Gram-positive bacteria 11.49%. The antibiotic susceptibility pattern ensures that imipenem has the highest sensitivity rate in all uropathogens among all the other antibiotics while penicillin shows the great resistance in all the organisms compared with other antibiotics. The other antibiotics such as linezolid, vancomycin, amikacin, tetracycline, and meropenem are recommended for the treatment. The prevention of development of multidrug resistant organisms by giving the correct treatment and following the hygienic conditions is the best way to prevent the UTI.